ANALISIS PENDAPATAN PETANI PEPAYA DI KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Rahmadi Syakban; Riska Dian Oktari; Elfi Rahmadani; Yusmar Mahmud (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2023)
This research aims to determine the income of papaya farmers in Pasir Penyu District, Indragiri Hulu Regency. The data used in this study are primary data and secondary data. Primary data was obtained from interviews with 15 sample farmers, while secondary data was obtained from the Central Bureau of Statistics and the Department of Agriculture of Indragiri Hulu Regency. Data analysis used in this research is descriptive quantitative by calculating the costs incurred by farmers, farmer income and business feasibility analysis. The research results show that the average fixed cost of papaya farming is IDR. 2,162,600.00 per month. Meanwhile, the average variable cost for farmers is Rp. 4,587,000.00 per month. The net income of papaya farmers is Rp. 2,418,400.00 per month with an RCR value of 1.23.